Bound phenolic compounds of whole cereals grain as a functional food component: part one - Petra TERPINC (Acta Agriculturae Slovenica)
Numerous metabolic diseases are nowadays associated with an unbalanced energy-rich diet, depleted from dietary fibers and other protective bioactive compounds. Given the limited success of therapeutic interventions to treat obesity and the metabolic syndrome, there has been an increased interest in other strategies. In part one, the focus is made on a role of whole cereals grain in diet, the most important bioactive components and their distribution in grains. We find out, that bran, a by-product of the grain processing industry, represents an unexploited source of phenolic compounds. Their biosynthesis takes place on the endoplasmic reticulum and other plant organelles from which they are transported to other cellular compartments. Deamination, hydroxylation and methylation are the main reactions involved in the formation of hydroxybenzoic and hydroxycinnamic acids. Special emphasis is made on phenolic compounds which remain in the solid residue after aqueous-organic solvent extraction. Non-extractable phenolic compounds are covalently bound to the cell wall materials, consequently the amount of bioactive compounds in cereals are often underestimated. Ferulic acid, as the most important representative, may acts against disorders related to oxidative stress, including cancer, diabetes and neurodegenerative diseases. Insoluble bound phenolic compounds are not degraded in the digestive tract, they are absorbed into the bloodstream as different metabolites after they are subjected to fermentation by the intestinal microflora. Adequate consumption of bound phenolic compounds can lead to improve antioxidant and anti-inflammatory properties, and there are many evidences suggesting their role in intestinal diseases prevention.